Prevalence and determinants of under-five mortality (U5M) in low-and lower -middle-income countries: Evidence from recent demographic and health surveys - Md. Alamgir Sarder; Tabassum Mehedi; Benojir Ahammed; Md. Khairul Islam; Subarna Kundu; Murfia Muna; Maliha Mahajabin (PLoS ONE, 2025)
Objectives Under-five mortality (U5M) remains a major global challenge, particularly in low-and lower-middle- income countries (LLMICs) where healthcare disparities are prevalent. This study evaluates the prevalence of U5M and examines the relative importance of its associated factors across 32 LLMICs. Methods Data from the Demographic and Health Survey (2011–2024) were used for analysis. A total of 266,333 children under five years of age were included to assess the association of 20 factors at both individual and community levels with U5M. The chi-square test and multivariate logistic regression model were applied to determine the association of these factors with U5M. Results Among the children aged 0−59 months, the prevalence of U5M was 40.5 per 1,000 (95% CI: 39.8–41.2). In the pooled sample, at the individual level, family member (>7) was the strongest factor associated with U5M (adjusted odds ratio (AOR):1.27; 95% CI:1.22–1.33, p < 0.001), followed by maternal age ≥ 35 years (AOR: 1.25; 95% CI:1.20–1.30, p < 0.001), being a female child (AOR:1.19; 95% CI:1.15–1.24, p < 0.001), and maternal unemployment (AOR:1.10; 95% CI:1.05–1.14, p < 0.001). At the community level, high maternal illiteracy (AOR:1.52; 95% CI:1.35–1.70, p < 0.001) was the most significant factor, followed by rural residence (AOR:1.26; 95% CI:1.15–1.38, p < 0.001), high paternal illiteracy (AOR:1.20; 95% CI:1.10–1.30, p < 0.001), and high maternal unemployment (AOR: 1.10; 95% CI:1.02–1.20, p < 0.001). Furthermore, large family members at individual levels and high maternal illiteracy at the community level consistently rank among the top two strongest factors across most countries, with a few exceptions. Conclusions In LLMICs, U5M remains high, strongly associated with large family size and high maternal illiteracy. Governments and non-governmental organizations should promote maternal education and contraception use to facilitate birth spacing and family planning, while tailoring interventions to country-specific contexts.